GAYA KEPEMIMPINAN PRESIDEN INDONESIA - Syugiarto; Nasir Mangngasing (DAS Institute, 2022)
This study examines the leadership styles of seven Indonesian presidents, from President Soekarno to President Joko Widodo. The method used in this study is a literature review. The theory used in this study is the theory proposed by Northouse (2016) which explains 15 leadership styles, namely: Trait Approach, Skill Approach, Behavioral Approach, Situational Approach, Path-Goal Theory, Leader-Member Exchange Theory, Transformational Leadership, Authentic Leadership, Servant Leadership, Adaptive Leadership, Psychodynamic Approach, Leadership Ethics, Team Leadership, Gender and Leadership, and Culture and Leadership. The results of this study indicate that the leadership styles shown by the seven Indonesian presidents are different from one another. President Soekarno is identical with the Trait Approach leadership style, President Soeharto with Path-Goal Theory leadership style, President BJ Habibie with Behavioral Approach leadership style, President Abdurahman Wahid with Skill Approach leadership style, President Megawati Soekarno Putri with Gender and Leadership leadership style, and President Joko Widodo with the leadership style of Servant Leadership